Multimodal Discourse Analysis on Mie Sedaap Singapore Spicy Laksa Advertisement - Darmapatni , Ni Nyoman Sindu (Jurnal Penelitian Mahasiswa Indonesia, 2023)
This study discusses the multimodal analysis on Mie Sedaap Singapore Spicy Laksa. As we know, both in printed or electronic advertisement is a discourse that has a complex message. This complexity happens caused by the companies that try to deliver the message to the customers. In order to make the message clearly conveyed to the customers, there are several things that need to be considered such as language features and also other visual features. Therefore, an Multimodal Discourse Analysis is needed in order to get the meaning and understand the complexity in Mie Sedaap Singapore Spicy Laksa. The multimodal analysis being discussed in this study is using functional systemic linguistics theories from Halliday (1975) cited in (Juliana and Arafah, 2018). This multimodal analysis was developed by the combination of the multimodal theory (Anstey & Bull, 2010, cited in Raharjo, et all, 2020), and multimodal analysis by Kress and Van Leeuwen (1996-2006) cited in (Pratiwy & Wulan, 2018), as well as to explain the multimodal analysis of researchers using a semiotic approach to Mie Sedaap Singapore Spicy Laksa Advertisement.